Indian Higher Education Reform: From Half-Baked Socialism to Half-Baked Capitalism - Devesh Kapu and Pratap Bhanu Mehta (CID Working Paper No. 108, 2004)
This paper examines the political economy of Indian higher (tertiary) education. We first provide an empirical mapping of Indian higher education and demonstrate that higher education in India is being de facto privatized on a massive scale. But this privatization is not a result of changing ideological commitments of the key actors-the state, the judiciary or India's propertied classes. Rather, this privatization has resulted from a breakdown of the state system and an exit of Indian elites from public institutions, to both private sector institutions within the country as well as abroad. Private philanthropy in higher education, which was supportive of public institutions in the past, is also increasingly withdrawing its support. Consequently the ideological and institutional underpinnings of this form of privatization remain exceedingly weak. The paper questions the extent to which the political economy of Indian higher education can be explained by the hypothesis of "middle class capture" and suggests that education policy, far from serving the interests of the middle class, is actually driven by a combination of ideology and vested interests. We also examine the role of the judiciary in shaping the regulatory landscape of Indian higher education and argue that it an important actor shaping the regulatory landscape of higher education, but in a manner that has done as much to confuse as clarify. Instead of being part of a comprehensive program of education reform, private initiatives remain hostage to the discretionary actions of the state. As a result, the education system remains suspended between over-regulation by the state on the one hand, and a discretionary privatization that is unable to mobilize private capital in productive ways. The result is a sub-optimal structuring of higher education. The most potent consequence of this is a secession of the middle class-ironically the very class whose interests these institutions were supposed to serve-from a stake in public institutions.